2008
DOI: 10.3748/wjg.14.5059
|View full text |Cite
|
Sign up to set email alerts
|

Cellular DNA repair cofactors affecting hepatitis B virus infection and replication

Abstract: AIM:To investigate whether hepatitis B virus (HBV) infection activates DNA damage response and DNA repair cofactors inhibit HBV infection and replication. METHODS: Human hepatocyte cell line HL7702 was studied. Immunoblotting was performed to test the expression of ataxia telangiectasia-mutated (ATM)-Rad3-related protein (ATR), p21 and the level of phosphorylation of Chk1, p53, H2AX, ATM in HBVinfected or non-infected-cells. Special short RNAi oligos was transfected to induce transient ATR knockdown in HL7702.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…Therefore, it will be interesting to evaluate, whether efficient repair system in crustaceans can protect these organisms from infections. Previous studies indicate that, DNA repair proteins may suppress viral infections, in higher organisms 49 . Studies suggest that DNA repair proteins may inhibit and can have an effect on retrotransposons and viral infections in yeast and mammals 50 – 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it will be interesting to evaluate, whether efficient repair system in crustaceans can protect these organisms from infections. Previous studies indicate that, DNA repair proteins may suppress viral infections, in higher organisms 49 . Studies suggest that DNA repair proteins may inhibit and can have an effect on retrotransposons and viral infections in yeast and mammals 50 – 52 .…”
Section: Discussionmentioning
confidence: 99%
“…DNA repair protein in higher organisms suppresses the viral infection instead of leading to establishment is partially observed. It has been demonstrated that DNA repair molecules inhibit and down‐regulate hepatitis B virus replication in mammals (Zhao et al. 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanically, p53 can directly suppress HBV replication by binding and repressing the HBV enhancer 45 . Recently, Ying Yan et al 42 proposed a new mechanism that p53 controls HBV infection; they found that p53 can inhibit the entry of HBV into hepatocytes by binding to sodium taurocholate cotransporting polypeptide (NTCP) promoter region (which is the key receptor to recognize HBV hepatocytes) and thereby inhibiting NTCP synthesis.…”
Section: Hbv-induced Hepatoma Cell Transformationmentioning
confidence: 99%